Effect of Water Absorption on Mechanical Properties of Calotropis Procera Fiber Reinforced Polymer Composites - Raghu M J; Govardhan Goud (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2020)
The present work investigates the effect of water absorption on mechanical properties of calotropis procera fiber reinforced epoxy polymer composites. The calotropis procera fiber chemical and mechanical testing was done to evaluate chemical composition and strength of the fiber. The composites are fabricated by reinforcing calotropis procera fiber in epoxy matrix by varying the fiber wt. % by traditional hand layup method. The water absorption of calotropis procera reinforced epoxy polymer composites at room temperature was found to increase with increasing fiber loading. The mechanical testing results of moisture exposed composites indicated decreased strength which may be due to degraded bonding between fiber and matrix.